Knowledge and attitude towards identification of systemic inflammatory response syndrome (SIRS) and sepsis among emergency personnel in tertiary teaching hospital - Abdul Rahman, Nurul 'Inayati; Chong, Mei Chan; Zakaria, Mohd Idzwan; Jaafar, Mohd Johar (Elsevier Australia, 2019)
Introduction: An emergency department (ED) is often the first point of medical contact for sepsis patient, which plays an important role in early identification and management of high-risk septic patients. The present study was aim to evaluate emergency personnel’s knowledge and attitude toward identification and management of systemic inflammatory response syndrome (SIRS) and sepsis. Methods: This cross-sectional study was conducted in a tertiary teaching hospital and recruited all emergency personnel. A validated questionnaire on knowledge and attitude towards identification and management of SIRS/sepsis was distributed among 120 emergency personnel. Data were analyzed using descriptive and inferential statistics. Results: Overall finding founds emergency nurses and assistant medical officer appeared to have moder- ate knowledge in several important areas of SIRS/sepsis identification and management. Majority of the emergency personnel have neutral attitudes, as they do not give enough importance towards identifica- tion of patients with SIRS and sepsis. The present study finding found that knowledge of clinical criteria and management of SIRS/sepsis was highest among assistant medical officers (p = 0.02) and bachelor’s degree holders (p=0.02) with emergency experience more than 5 years (p=0.03). A trend toward an increase in knowledge of SIRS and sepsis is significantly correlated with positive attitudes. Conclusion: The emergency personnel demonstrated a moderate knowledge and neutral attitude toward identification and management of SIRS and sepsis. Therefore, the awareness and knowledge of SIRS and sepsis should be enhanced among emergency personnel in order to improve outcome